1982
DOI: 10.1104/pp.69.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Metabolic Activity of Lemon Juice Vesicle Explants in Vitro

Abstract: Actively growing juice-vesicle explants, established from smaDl lemon (Cits lmon L. Burm. f. var. 'Eureka') fruits, were cultured in vitro on defined media. The juice vesicles continued to enlarge in culture for several months, without caDlus proliferation, and their initial growth was promoted by indoleacetic acid, gibberellic acid, and N-benzyladenine.The metabolic competence of the explants, and its relevance to whole fruit development, was further investigated. Juice vesicles continued to accumulate protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

1987
1987
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 17 publications
0
7
1
Order By: Relevance
“…The order of juice vesicle stimulation (i.e. fresh weight increases) was GA3 > 6-BAP > IAA > basal medium [2]. In contrast, we found the order of benefit using growth regulators was as follows: IAA > ABA > basal medium > GA3 > 6-BAP (Table 2).…”
Section: Discussioncontrasting
confidence: 43%
See 4 more Smart Citations
“…The order of juice vesicle stimulation (i.e. fresh weight increases) was GA3 > 6-BAP > IAA > basal medium [2]. In contrast, we found the order of benefit using growth regulators was as follows: IAA > ABA > basal medium > GA3 > 6-BAP (Table 2).…”
Section: Discussioncontrasting
confidence: 43%
“…Altman, Gulsen and Goren [2] and Gulsen, Altman and Goren [6] reported that juice vesicles could be cultured several months on nutrient medium containing MS salts, 5% sucrose, and 0.01 mM GA3, 6-BAP, or IAA. The order of juice vesicle stimulation (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations